Kesan halaju putaran gilapan terhadap peratus potongan hujung sisi pandu gelombang polimer SU-8 di atas substrat silikon - Mohammad Syuhaimi Ab Rahman; Fazlinda Ab Aziz; Noor Azie Azura Mohd Arif; Abang Anuar (2009)
This research have focused on polishing characterize of polymer based waveguides. The aims of this research are to study how polishing rotation speeds affect the length of cut end face SU-8 polymer on silicon substrate. There are seven sets of rotation velocities which are 50, 100, 150, 200, 250, 300, and 350 rpm. From the obtained result, it can be concluded that percentage of cut length for each rotation velocity is ≤ 0.5 % (50 rpm), 0.6 – 1.0 % (100 rpm), 3.8 – 4.8 % (150 rpm), 7.7 – 10.6 % (200 rpm), 15.7 – 18.3% (250 rpm), 25.6 – 27.4 % (300rpm) and 40.0 – 43.7 % (350 rpm).